Analisa Beban Kerja Mental menggunakan Metode NASA TLX pada Departemen Logistik di PT XYZ - Santoso, Nur Rochman Dwi; Kusnadi, Kusnadi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT XYZ is a manufacturing company that has facilities to produce a variety of specialized chemicals that are used in various industries. Employees of the Logistics Department at PT. XYZ often have difficulties in completing their tasks according to the scheduled schedule. This situation often makes them work overtime to finish the work that's stacked. The requirement to ensure timely delivery and effective coordination with customers adds to their mental workload. In an attempt to determine the level of mental workload of the logistics department employees, a measurement of the mental labor load was carried out using the NASA TLX method. Based on the results of the measurements obtained, the result of the calculation of the average score of the total staff of the Logistics Department of 66.22 indicates that the classification of the overall mental work load of the employees included in the high level. The most influential indicators of mental workload in this study are mental demand, physical demand, and own performance.